Effects of Genotype, Season and Nutrition on Sunflower Yield and Hollow Seededness in Gezira (Sudan) - Younis Mohamed, Mohamed; S. Ibrahim, Abu Elhassan; N. Elzein, Ibrahim (Gezira Journal of Agricultural Science; Vol 1 No 1 (2003), 2021)
A field experiment was conducted to study the effects of genotype, season and nutrition on sunflower seed yield and hollow seededness in Gezira. Five sunflower cultivars (Damazin-l, Hungarian-A, Rodio, Hysun-25 and Hysun-33), two nitrogen levels (0 and 129 kgN/ha) and two levels of phosphorus  (0 and 129 kg P 2 0 5 /ha) were used over two seasons (autumn and winter 2000) in a randomized complete block design with four replications. Data on 14 characters were collected. results showed that the percentage of empty seeds, self-compatibility 1000-seed weight and seed yield were significantly affected by and its interaction with season. The means of these characters were relatively higher in winter than in autumn season except for the empty seeds. The application of high doses of fertilizer had no significant effect on the percentage of empty seeds, and consequently lie phenomenon of empty seeds could be attributed mainly to genetical  and seasonal effects. The genotypes mean seed yields ranged from 1127 to 1899 kg/ha, with Hysun-33 giving the highest yield. Simple  and genotypic correlation analyses emphasized that seed yield was and positively correlated with days to flowering, harvest index , head diameter, seed number/head, self-compatibility, number filled seeds/head and percent seed set. Both analyses showed negative coefficients between seed yield and empty seeds. The percentage of empty seeds was positively and significantly correlated with plant height and number of heads/plant. The path analysis indicated that head diameter, percentage of seed set, days to flowering and seed weight  were the most important traits related to seed yield where as percentage of seed set, harvest index, and days to maturity were the  most important traits contributing to high degree of self-compatibility in sunflowe